Machine learning meets medical imaging : first International Workshop, MLMMI 2015, held in conjunction with ICML 2015, Lille, France, July 11, 2015, Revised selected papers /: first International Workshop, MLMMI 2015, held in conjunction with ICML 2015, Lille, France, July 11, 2015, Revised selected papers. (2015) - Unknown
No abstract available